New distribution records of Bohemian Waxwing Bombycilla garrulus (Linnaeus, 1758) from Turkey - Karataş, Ahmet; Bulut, Şafak; Karataş, Ayşegül (Universitatea din Oradea, 2019)
The Bohemian Waxwing (Bombycilla garrulus Linnaeus, 1758) is a rare and high irregular migrant in Turkey. Most of records from the country have been taken in winter season. In this study, four winter and one spring observations were reported from five new localities. In additionally, some information on its ecology, behaviour and subspecific status were given. ©Biharean Biologist, Oradea, Romania, 2019 2-s2.0-85072088073